Edukasi Dan Skrining Gula Darah Dan Anemia Dalam Rangka Mencegah Terjadinya Kulit Kering Pada Kelompok Lanjut Usia - Linda Yulianti W; Fiona Valencia Setiawan; Friliesa Averina; Farell Christian Gunaidi (Universitas Muhammadiyah Manado, 2024)
Xerosis or dry skin occurs when the skin loses moisture, causing itching, cracking and dullness. This condition is common in the elderly due to physiological changes such as decreased activity of the sebaceous and sweat glands, as well as impaired skin barrier function. Anemia and uncontrolled blood sugar levels can worsen dry skin conditions in the elderly. Therefore, this community service activity was carried out with the aim of increasing awareness of the elderly about the importance of maintaining healthy skin related to anemia and blood sugar. This activity includes education about preventing and managing dry skin, controlling blood sugar, and treating anemia. This activity uses the PDCA method to ensure that the activity process runs systematically and can be evaluated. The results of the activity showed that the majority of participants experienced mild anemia and a small number had abnormal blood sugar. This shows that intervention and health education are needed for the elderly group to improve their quality of life by maintaining hydration of their skin.